2023
DOI: 10.12681/jhvms.27509
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of buparvaquone and paromomycin on oocyst excretion and clinical parameters in diarrheal calves naturally infected with cryptosporidiosis

Abstract: Cryptosporidium is an obligate intracellular parasite that infects a wide variety of hosts. Twenty calves with cryptosporidiosis were divided into two groups. A single dose of 2.5 mg/kg buparvaquone was administered intramuscularly to one group, while 100 mg/kg/day paromomycin was administered orally to the other group. The results obtained from the study in which oocyst shedding and clinical parameters of sucking reflex, mental status, oocyst scattering were observed in both groups offer an effective control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…32 These changes are probably related to the activity of buparvaquone on oocysts and the suppression of inflammatory mediators. 24 There was a statistically significant increase in LYM (×10 9 /L) values between the 3rd, and 7th day after treatment (p<0.05) (Table 1). Considering the NEU (×10 9 /L) values, a statistically significant increase was determined between the 0th and 3rd days of comparison (p<0.005) (Table 1).…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…32 These changes are probably related to the activity of buparvaquone on oocysts and the suppression of inflammatory mediators. 24 There was a statistically significant increase in LYM (×10 9 /L) values between the 3rd, and 7th day after treatment (p<0.05) (Table 1). Considering the NEU (×10 9 /L) values, a statistically significant increase was determined between the 0th and 3rd days of comparison (p<0.005) (Table 1).…”
Section: Resultsmentioning
confidence: 89%
“…21,22 It has been reported that the efficacy of buparvaquone, which is used in the treatment of neonatal calves naturally infected with cryptosporidiosis, on oocyst scattering is quite successful. 23,24 In the literature review, it was determined that the hemato-biochemical effects of the drug in calves with cryptosporidiosis were not investigated.…”
Section: Introductionmentioning
confidence: 99%